The use of a new high-speed shielded curved drill is associated with improved intraoperative and clinical outcomes after cervical corpectomy and fusion procedures: a retrospective case series - Peloza, John; Malone, Hani; Jacobian, Erel; Kolsky, Daniel E.; Harel, Ran; Guyer, Richard D.; Millgram, Michael A.; Ashkenazi, Ely (Journal of orthopaedic surgery and research, 2023)
Anterior cervical corpectomy and fusion (ACCF) is an effective technique to address multi-level degenerative cervical myelopathy. However, as the number of surgical levels increases, the outcomes worsen with respect to complication rates, range of motion and length of surgery. This study aimed to determine the clinical outcome of ACCF procedures performed using a new distally curved and shielded drilling device. A retrospective study was conducted on 43 ACCF procedures in which the device was used for osteophyte removal. Patient files were reviewed to assess the early clinical results and complications following ACCF. Clinical outcomes were evaluated using patient neck and arm pain scores and SF-36 questionnaires. Hospitalization characteristics were compared with historical controls. All procedures were uneventful and without major complications or neurological deterioration. Single-level ACCF procedures required an average of 71 min and followed by an average hospitalization of 3.3 days. Osteophyte removal, verified by intraoperative imaging, was satisfactory. Average neck pain score was improved by 0.9 points (p = 0.24). Average arm pain score was improved by 1.8 points (p = 0.06). SF-36 scores were improved in all domains. The new curved device enabled safe and efficient removal of osteophytes sparing adjacent vertebral removal in ACCF procedures, thus improving the clinical outcome.